A piezoelectric sensing neuron and resonance synchronization between auditory neurons under stimulus. (April 2021) - Zhou, Ping; Yao, Zhao; Ma, Jun; Zhu, Zhigang
Highlights: A new auditory neural circuit is presented. A functional neuron model is obtained. Two auditory neurons reach resonance synchronization without synapse coupling. Abstract: A piezoelectric ceramic can convert external mechanical force and vibration into electric signals by producing distinct output voltage when certain deformation is induced. As a result, a piezoelectric ceramic in nonlinear circuit can be used as sensitive sensor for detecting external sound signals. In this paper, a piezoelectric ceramic is incorporated into a simple FithzHugh–Nagumo neural circuit for capturing and encoding external sound signals. The improved neural circuit and functional neuron models are obtained, and a variety of firing modes are reproduced in the neural activities by changing the external sound signals. For animals, two ears can receive and encode the external sound signals synchronously in effective way, and thus the synchronization between two auditory neurons. To explore the capacity of discernment and cooperation of two ears in the auditory system when external voice is applied, two piezoelectric sensing neurons (PSNs) are driven by the same external voice for detecting possible synchronization approach without any synapse coupling. It is found that two identical PSNs driven by the same periodical stimuli (external forces) can reach synchronous bursting, spiking, and periodical firings, respectively. In case of chaotic firing, the synchronization stability is dependent on the external forcing applied on the two PSNs. Furthermore, external additive noise is applied for considering stochastic forcing on the PSN, it is confirmed that two identical PSNs can reach kinds of synchronous firings, while some intermediate noise intensities seldom enhance the synchronization stability between two identical PSNs. The Hamilton energy in isolated PSN driven by external forcing is estimated, and this kind of non-coupling synchronization is explained as a kind of resonance synchronization. These results can be helpful to design functional auxiliary devices for those patients with hearing impairment.